An Algorithm for Forensic Examination of Documents Containing Entries Written in Sympathetic Inks - A. V. Efimenko; P. A. Chetverkin (Теория и практика судебной экспертизы)
The article presents the results of experimental studies on the detection of handwritten entries made with sympathetic inks, and a forensic algorithm for the examination of such documents.